Comparison of the effects of acute and regular exercise on intraocular pressure in Turkish athlete and sedentarians - Ozmerdivenli, R; Simsek, E; Bulut, S; Karacabey, K; Saygin, O (Taylor & Francis Ltd, 2006)
The aim of this study was to investigate the changes that take place in IOP in athletes and people leading sedentary lives subjected to aerobic and anaerobic exercise and how chronic exercise could affect these changes. The study included 20 sportsmen (Group 1), and 20 people leading sedentary lives (Group 2). The intensity of the exercise for both groups was determined according to the Karvonen protocol and executed as an aerobic exercise program involving running on a treadmill for 30 min. Subjects in both groups were subjected to anaerobic exercise according to the Wingate test protocol for 30 s. The intraocular pressure of all subjects before exercise and after aerobic and anaerobic exercise were measured. The IOP before and after exercise aerobic and anaerobic were evaluated by the Willcoxon test whereas the right and left IOP before exercise and after the aerobic and anaerobic exercise programs in both groups were evaluated using the Mann Whitney U test. p values of <.05 were considered significant. Significant differences were found when the pre-exercise and post-aerobic and anaerobic exercise IOPs of the groups were compared (p < .05). Comparison of the post-anaerobic and aerobic exercise revealed a fall in the IOPs of the subjects after the aerobic exercise (p < .01). In this study, exercise was found to lead to a fall in the IOP in both sportsmen and those leading sedentary lives with the fall less apparent under anaerobic conditions than under aerobic conditions. In conclusion, therefore, it can be said that in those with an increased intraocular pressure, regular, moderately intense aerobic exercise rather than short-lived intense exercise could be more useful.
Keywords: exercise; intraocular pressure; performance; Turkish athlete